2016
DOI: 10.1016/j.polymer.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Radical mediated thiol-ene/yne dispersion polymerizations

Abstract: We report the synthesis of polymeric particles using radical mediated step-growth thiolene and thiol-yne "click" dispersion polymerizations in alcoholic solvents. Various alkene, alkyne and thiol monomers were used, and thermal, photo-or redox initiation methods were all shown to be effective means to initiate polymerization. Polymer particles typically were formed with diameters in the range of several hundred nanometers, with narrow size distributions though broader than typical free-radical chain-growth dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Addition of a single thiol to a cycloalkyne is relatively rapid and this reaction can be performed spontaneously even in the absence of light and photoinitiator in an unpurged atmosphere. Cyclooctynes used for SPAAC (shown in Figure S1 in the Supporting Information) can be usable for doing click reaction with thiol as well …”
Section: Introductionmentioning
confidence: 99%
“…Addition of a single thiol to a cycloalkyne is relatively rapid and this reaction can be performed spontaneously even in the absence of light and photoinitiator in an unpurged atmosphere. Cyclooctynes used for SPAAC (shown in Figure S1 in the Supporting Information) can be usable for doing click reaction with thiol as well …”
Section: Introductionmentioning
confidence: 99%
“…Previously, we and others developed radical‐mediated thiol‐ene and thiol‐yne polymerizations for the production of colloidal polymer particles . Synthesis of colloidal polymers have been shown to work in different dispersed polymerization modes, such as emulsions, dispersions, miniemulsions and suspensions . In these prior cases, the particles were emulsified or stabilized using common surfactants, such as sodium dodecyl sulfate (SDS), or natural gums .…”
Section: Introductionmentioning
confidence: 99%
“…Tyson et al reported thiol‐ene reactions initiated by visible light in presence of a transition metal polypyridyl photocatalyst and p ‐toluidine as an additive. Critically, thiol‐ene chemistry is widely used for a variety of applications such as the synthesis of crosslinked functional polymeric microspheres as well as the functionalization of microspheres . Dispersion polymerization based on thiol‐ene/thiol‐yne chemistry features some characteristics associated with the “click” principle, i.e., high reactivity with monomers, excellent yields, selectivity, and reaction orthogonality .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bowman and co‐workers synthesized photoresponsive polymeric particles by photoinduced nitrile imine‐mediated tetrazole‐ene cycloaddition (NITEC) and thiol‐Michael addition dispersion polymerization in which the polymeric particles feature an inherent tetrazole‐ene functionality for postparticle formation chemistry. Alimohammadi et al synthesized polymeric particles by thiol‐ene and thiol‐yne free radical dispersion polymerization studying the effect of initiator (photo, thermal, and redox) on the particle size. Durham et al synthesized polymeric microspheres using thiol‐ene/thiol‐yne suspension polymerization in presence of thermal and photoinitiator, while Tan et al developed porous polymer particles using water born thiol‐ene suspension polymerization and studied the effect of polymerization conditions and porogen amounts on the morphology of particles and their sizes.…”
Section: Introductionmentioning
confidence: 99%